(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article is devoted to the study of epidemiological and etiological data of morphogenesis and pathomorphology of congenital heart defects in children. Modern data on the etiology and pathophysiological mechanisms of the development of this pathology are considered. A brief review of the literature on this issue was carried out.